OVERVIEW OF HOSPITAL SPIRITUAL PREACH GUIDELINES IMPLEMENTATION BY EMPLOYEES OF THE MUHAMMADIYAH GENERAL HOSPITAL NORTH SUMATERA IN 2019 - ANDRE FADILLAH; ELMAN BOY (JURNAL ILMIAH MAKSITEK, 2020)
Implementation of Islamic Sharia in hospitals is not an easy thing, many factors can hamper the implementation. Theproblem can be from the demands of the hospital staff, lack of confidence in carrying out tasks, and lack of nurses at thehospital. Seeing the importance of knowledge about religion, this attracted the attention of the Muhammadiyah Organizationto make business charity in the health facilities sector. Descriptive with qualitative descriptive design. The samplingtechnique used is total sampling by taking all populations into a sample, as many as 52 people. Based on the results of thestudy, it is known that the da'wah guidelines carried out on the highest respondents were statements number 1 (98.1%) and21 (98.1%). While the most da'wah guidelines that were not carried out on respondents were statements 6 (31%), and 14(14.3%). Based on the results of the study about description of the implementation of the hospital da'wah guidelines at theMuhammadiyah General Hospital in Sumatra, it can be concluded that most of the hospital preaching guidelines have beenimplemented but there are still some that have not been implemented.